Project & trade finance : 1994 handbook - Euromoney Publications PLC.; West Merchant Bank.; Milbank, Tweed, Hadley & McCloy (West Sussex : Euromoney Publications, 1994)
This book is an easy reference guide to the world of project and trade finance.
1994 handbook.
hza 29/01/2019
Loans
Keywords: Export credit; Industrial development projects; Export credit; Financial institutions